Clinical profile of patients with vernal keratoconjunctivitis - Jivangi, Vivekanand S.; Raikar, Hemalatha A.; Khatib, Zain I.; MN, Abhilasha; Suhana, Ayisha (International Journal of Research in Medical Sciences, 2017)
Background: Ocular allergy is a common disorder, which can be debilitating for patients and at times challenging physicians to diagnose and treat. Allergic disease affects 30-50% of the population. Vernal keratoconjunctivitis (VKC) has predilection for young age group and the diagnosis is generally based on signs and symptoms of the disease. This study was undertaken to stress upon the disease and those secondary to its long-term medication. Methods: 74 patients with VKC detected at random, who attended the Department of Ophthalmology KIMS, Hubli from December 2012 to May 2014. The relevant details of history and clinical examination of the patients were recorded on a specifically designed Proforma. The type and severity of VKC was noted. Clinical observation and evaluation of clinical signs and symptoms were performed before and after drug therapy at first visit, weekly interval for 2 weeks and at the end of 3 months. Results: 22 out of 74 (29.72%) were in the 6-10 years of age. The male: female ratio was 2.7:1.13. Majority of the patients presented in the month of May. Family history of allergy was present in 4 (5.04%) of patients. 59 (72.72%) patients showed seasonal symptoms and 15 (20.27%) patients showed perennial symptoms. Mixed type was found in 60.81%. Itching was present in 59 (79.72%). 72 (97.29%) had papillae on the upper tarsal conjunctiva. Conclusions: VKC was common in males, during hot climate. Mixed type of VKC was more commonly present.